Potensi pengembangan bahasa Indonesia menjadi bahasa internasional - Handoko, Muawal Panji; Fahmi, Royan Nur; Kurniawan, Ferry Yun; Artating, Hardina; Sinaga, Meili S. (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
Research on development potential of language Indonesia became the international language through teaching, this BIPA exposed about the average amount of students and his enthusiasm in the 23 country targets. We intend it to find out which countries have a great interest in this amount of students seen from the BIPA to be adjusted to the number of teachers who will be sent to the target country. The existence of the average amount of students can also known to target countries with a population of students which is so that the future can be PPSDK to restrict the policy directions of teachers who will be sent to these countries as the form of effectiveness and efficiency. Results of the study showed that Thailand, Myanmar, New Guinea, Australia, and East Timor is five countries with the potential and the average highest BIPA students.